EFFECT OF ORGANIC ACID AND STEAMING TREATMENTS ON CHITIN CONTENT AND NUTRITIONAL QUALITY OF Hermetia illucens LARVAE AS BROILER FEED - Warisman; Harry Agusnar; Ma'ruf Tafsin; Yunilas (Journal of Animal and Plant Sciences, 2024)
Chitin, an anti-nutritional factor, hinders nutrient absorption in animal feed. Its presence in Black Soldier Fly (Hermetia illucens L.) larvae limits feed utilization in broiler chickens due to its indigestibility and nutrient-binding properties that may deter growth of animals. This study aimed to modify the chitin content by applying physical and chemical treatments to raw Hermetia illucens L. (BSF) larvae, addressing the nutritional aspects of the feed. The research design employed was a complete randomized factorial design with three factors and three replications. Factor 1 included Control (C) and Steaming (S) as physical treatments, Factor 2 involved the use of three organic acids, i.e. acetic acid (A), citric acid (C), and propionic acid (P), and Factor 3 included three concentrations, namely 2%, 4%, and 6%. Broiler chickens (n = 54) were exposed to feed resulting from the physicochemical treatment of BSF larvae. Chemical treatment significantly influenced most parameters and was not heavily dependent on concentration. Acetic acid emerged as the best organic acid in enhancing the nutritional profile of the feed product while simultaneously yielding the lowest chitin content. Confirmation through biological parameters indicated that treatment with acetic acid resulted in improved digestibility, including crude protein and organic matter. Correlation results further affirmed thatchitin content influences feed digestibility and remains a challenge to be addressed. The best physicochemical treatment for post-processed BSF larvae was the control (non-steamed) treatment with 2% acetic acid with reduced chitin content and improved digestibility and other nutritional parameters.
Keywords: Acetic acid; Chitin; Digestibility; Spearman’s correlation coefficients